Building a Prevention Clinic at the Northport VA to Improve Pneumonia Vaccination Numbers - Namita Akolkar, MD, MPH; Danielle K. Craigg, MD, MPH; Lisa Fisher, MD (Elsevier, 2024)
Introduction: Pneumonia vaccination rates have increased to >60% over the last 20 years. At the Long Island, New York, Northport VA Hospital, pneumonia vaccination data from 2021 showed a vaccination rate of 68.55%. The goal is a pneumonia vaccination rate of 85%. Pneumonia vaccines prevent invasive pneumococcal disease and pneumococcal pneumonia. The authors aimed to increase vaccination rates at Northport. Methods: The authors established a weekly vaccine and prevention clinic aiming to vaccinate as many veterans as possible. Preventive medicine residents performed outreach, scheduling, vaccine administration, and Brief Action Planning. Motivational interviewing techniques were used in outreach calls and clinic visits to encourage behavioral change. Results: From an outreach list >7,000 patients, 506 patients were contacted and counseled on pneumonia vaccination. A total of 130 patients were scheduled for clinic visits. Of these 130, 91 kept their appointments and were seen in the clinic, and 87 vaccines were administered, of which 56 were pneumonia vaccines. Data were collected and analyzed in 2022. Conclusions: Implementing a dedicated vaccine and prevention clinic using motivational interviewing techniques in outreach and clinical visits allows for optimized patient vaccinations, enhanced information sharing, increased primary care retention, and increasing visibility of preventive medicine among patients and colleagues within the Veterans Affairs medical system.